Unraveling the uptake mechanisms of mannan nanogel in bone-marrow-derived macrophages - Ferreira, Sílvia A. (2012)
The mechanisms associated with the cellular internalization of nanomedicines must be carefully considered when designing drug- and vaccine-delivery systems. The cellular fate and effects of nanomedicines depend to a large extent on the cell uptake routes. A self-assembled mannan nanogel is developed as a vaccination platform for antigen and adjuvant delivery. The mannan nanogel uptake by murine bone-marrow-derived macrophages is found to be time-, concentration-, and energy-dependent, involving mannose-receptor-mediated phagocytosis and clathrin-mediated endocytosis. The nanogel is also visualized in the cytosol suggesting endolysosomal escape. These results indicate that mannan nanogel is a promising versatile carrier for intracellular delivery of vaccines or therapeutic agents.